TRANSFORMATIVE CREATURES: THEOLOGY, GENDER DIVERSITY, AND HUMAN IDENTITY: with Finley Lawson, "Science, Religion, and Human Identity: Contributions from the Science and Religion Forum"; Susannah Cornwall, "Transformative Creatures: Theology, Gender Diversity, and Human Identity"; Joanna Collicutt, "Religion, Brains, and Persons: The Contribution of Neurology Patients and Clinicians to Understanding Human Faith"; Robert Lewis, "Humans as Interpretive Animals: A Phenomenological Understanding of Why Humans Bear God's Image"; Rebekah Wallace, "The Wholeness of Humanity: Coleridge, Cognition, and Holistic Perception"; James Thieke, "Energies and Personhood: A Christological Perspective on Human Identity"; and Emily Qureshi‐Hurst, "Can Sinners Really Change? Understanding Personal Salvation in the Block Universe.". Issue 3 (25th April 2022) - Cornwall, Susannah
Abstract: Gender transition may be figured as part of a broader creaturely process of being partners in our own becoming. Gender transition is explored through the lenses of transformation (including comparisons with theosis and with religious conversion) and neurodiversity. Humans are transformative creatures; trans and gender‐variant people, like others, have the power to curate their own identities and are on a journey toward perfection. Our nature as humans, including our sexed and gendered nature, is not over‐and‐done‐with. In this sense, our active building and shaping of our identities and body‐stories is not a rejection of a divine blueprint for human existence, nor an exercise of illegitimate human hubris, but rather a licit creaturely form of generativity.